DOE PRODUCTIVITY AND KID CROP OF ETAWAH GRADE DOES KEPT UNDER INDIVIDUAL AND GROUP HOUSING IN TURI SUB DISTRICT, SLEMAN DISTRICT - DIY PROVINCE - Rahim Aka (MEDIAGRO, 2008)
The research was conducted to investigate doe productivity and kid crop of Etawah Grade does under individual and group housing at Girikerto village, sub district of Turi, Sleman  -  DIY Province. Material consisted of farmers and their Etawah Grade does kept under individual and group housing. Descriptive and analytic survey method were applied to collect data. Purposive sampling method was applied to collect data. On average, 17 and 14 does and their kids respectively for group housing and individual management system were studied. Data  consisted  kid crop, litter size, kidding interval,  weaning weight, and doe productivity. Descriptive analysis was kid crop and to compare the kidding interval, litter size, weaning weights  and doe productivity  were analyzed using Independent Samples T-test  to identify differences between individual and group housing management systems.  The result showed that kid crop at group housing management system were  225.7% it was higher than those of individual management systems that is 176.6%.  Litter size and weaning weight were no significantly differ, while kidding interval and  doe productivity  differ (P<0.05) between both management systems.  It was concluded that  doe productivity and kid crop  of Etawah Grade does under group housing was better than individual management system.   Keywords:  Doe  productivity,  Kid  Crop,  Etawah  Grade goats,  group  and   Individual housing